2006
DOI: 10.4028/www.scientific.net/amr.11-12.243
|View full text |Cite
|
Sign up to set email alerts
|

PLLA/HA Electrospin Hybrid Nanofiber Scaffolds: Morphology, In Vitro Degradation and Cell Culture Potential

Abstract: Electrospinning has recently emerged as a potential technique for fabricating biomimetic tissue engineering scaffolds. In this study, Poly (l-lactic acid) (PLLA) /Nano-hydroxyapatite (HA) hybrid nanofibers scaffolds were prepared by electrospinning. The relationship between process parameters and fiber diameter has been investigated. The fiber diameter decreased with decreasing polymer concentration and with increasing electrospinning voltage; After 6 weeks of in vitro degradation, the mass, viscosity-average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
(13 reference statements)
2
6
0
Order By: Relevance
“…Similar results were reported by Wang and Norouzi et al for emulsion electrospinning [30,31]. containing chitosan nanoparticles was attributed only to chitosan degradation [34,[49][50][51]. As shown in Fig.…”
Section: Page 13 Of 32supporting
confidence: 93%
“…Similar results were reported by Wang and Norouzi et al for emulsion electrospinning [30,31]. containing chitosan nanoparticles was attributed only to chitosan degradation [34,[49][50][51]. As shown in Fig.…”
Section: Page 13 Of 32supporting
confidence: 93%
“…It was worth noting that the degradation rate of scaffold was greatly accelerated with the increase of PGA. Specifically, the 1PLLA/1PGA/HAP scaffold had 25.0 ± 4.2% weight loss, which was a little lower than that of the poly (D,L lactide-coglycolide (PLGA)/HAP scaffold or composite [ 45 , 46 ]. The results indicated that PGA regulated the degradation rate of scaffolds, which could be attributed to the fact that PGA's strong hydrophilicity leaded to self-degradation and increased the contact area between water molecules and PLLA chains, thus catalyzed the hydrolysis of PLLA.…”
Section: Resultsmentioning
confidence: 99%
“…Bone-like nHA/collagen composites have been developed previously by mineralizing the type I collagen sheet [13,14], though with mechanical properties that are too weak for practical applications. HA, though brittle by itself, has been used for bone regeneration and biomedical implant applications due to its biodegradability, bioactivity and osteoconductive properties [15]. Therefore, biocomposite nanofibers containing HA fabricated by electrospinning might be suitable as a scaffold with improved biological properties for bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%